Porosity analysis of polyamide-12 in multi jet fusion - Wang, Bin Hao (Nanyang Technological University, 2023)
Shrinkage is a prevalent problem in the field of additive manufacturing, some adverse effects of shrinkage include warpage and dimensional inaccuracy in the final product. To mitigate these effects, there is a need to study the shrinkages in PA12. Crystallisation shrinkage, which is one of the main contributing factors to the total shrinkage, have been extensively reported in research articles. Thus, this project aims to determine the shrinkage induced by the pores of Polyamide-12 (PA12) in Multi-Jet Fusion (MJF). Specimens were prepared using TMA machine under different heat rates, such that the number and size of pores are made distinct. It was observed that the specimens with slower heating rate having less pores, smaller total pore area and experiencing less shrinkage induced by pores. Whilst specimens with faster heating rate having more pores, larger total pore area and also experiencing larger shrinkages induced by pores.